Transient aerodynamics effect on V-tail aircraft in lateral stability - Nur Amalina Musa, 1987-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Doktor Falsafah (Kejuruteraan Mekanikal)) - Universiti Teknologi Malaysia, 2017